2015
DOI: 10.3389/fmicb.2015.01149
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil microeukaryotic communities to short-term fumigation-incubation revealed by MiSeq amplicon sequencing

Abstract: In soil microbiology, there is a “paradox” of soil organic carbon (SOC) mineralization, which is that even though chloroform fumigation destroys majority of the soil microbial biomass, SOC mineralization continues at the same rate as in the non-fumigated soil during the incubation period. Soil microeukaryotes as important SOC decomposers, however, their community-level responses to chloroform fumigation are not well understood. Using the 18S rRNA gene amplicon sequencing, we analyzed the composition, diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Eurotiomycetes was positively stimulated by fumigation. Many researchers concluded that Eurotiomycetes is capable of surviving in extreme conditions and produce extracellular and hydrolytic enzymes [30]. [31].…”
Section: Ilns Volume 74mentioning
confidence: 99%
“…Eurotiomycetes was positively stimulated by fumigation. Many researchers concluded that Eurotiomycetes is capable of surviving in extreme conditions and produce extracellular and hydrolytic enzymes [30]. [31].…”
Section: Ilns Volume 74mentioning
confidence: 99%
“…Most of the fungal population was eliminated and remained low for many weeks. Other work, using modern molecular methods (Dominguez-Mendoza et al, 2014;Chen et al, 2015), also showed that there are distinctly different microbial community structures in fumigated and non-fumigated soils.…”
Section: Controversy Over the Control In The Fi Methodsmentioning
confidence: 96%
“…It is theoretically possible that the community structure of the small recolonising microbial population is the same as that in the intact non-fumigated soil. However, Chen et al (2015) showed that the much diminished soil microbial biomass in the fumigated soil has a much smaller diversity (survivors mainly belong to the classes Bacilli, Eurotiomycetes and Sordariomycetes). Others have also shown vast differences in the community structure of pre-and post-fumigation populations (Reber, 1967;Dominguez-Mendoza et al, 2014).…”
Section: Why Is Som So Stable? the Regulatory Gate Hypothesismentioning
confidence: 99%
“…While there has been a surge of interest in viral diversity and ecology, there have been relatively few studies documenting bacterial-phage interactions in soil (12)(13)(14). Also present in soil are fungi, protists and larger organisms that have been documented via 18S rRNA gene sequencing (15,16) and more classical methods (17,18). While some studies have documented bipartite interactions, such as fungi-bacteria (19,20), bacteria-phage (12,21), plant-fungi (22,23), detailing complex multi-trophic interactions in soil remains a huge challenge.…”
Section: Introductionmentioning
confidence: 99%